Silent voices: Uncovering women’s absence in veterinary surgery publications - Kelly L. Bowlt Blacklock; Jill R. D. MacKay; Poppy Bristow; Ishita Parakh; Alina Paczesna; Fiona Mackay; Kathryn Pratschke (PLoS ONE, 2025)
Objective To determine the factors associated with an author being female in Veterinary Surgery journal publications from 2002 to 2023. Study design Retrospective observational study. Sample population A total of 2881 Veterinary Surgery papers published between 2002 and 2023. Methods Author gender was inferred using the Gender API and verified manually where necessary; only binary categories (male/female) were assigned. Statistical models (frequentist and Bayesian logistic regressions) were used to predict author gender based on publication year, author order (first, second, last), and surgical emphasis. Results Overall, 36% of the authors were female, with 43% of first authors, 37% of second authors, and 28% of last authors being women. The proportion of female first authors increased from 29% in 2010 to 60% in 2022, while female last authors ranged from 10% in 2002 to 36% in 2023. The likelihood of an author being female was influenced by the publication year, being the last author, and the subject of orthopaedics. Conclusion Compared with the demographics of the profession, women remain underrepresented in Veterinary Surgery authorships, particularly in senior author positions and orthopaedic papers. Disciplinary significance The underrepresentation of female authors highlights persistent gender disparities in veterinary surgery research. Further research is required to understand the factors that influence female authorship, so that institutions and journals can implement targeted initiatives to promote gender equity.